Ahmed Glaucoma Valve Implantation in Vitrectomized Eyes - Nimet Yeşim Erçalık; Serhat İmamoğlu (Journal of Ophthalmology)
Purpose. To evaluate the outcomes of Ahmed glaucoma valve (AGV) implantation in vitrectomized eyes. Materials and Methods. The medical records of 13 eyes that developed glaucoma due to emulsified silicon oil or neovascularization following pars plana vitrectomy and underwent AGV implantation were retrospectively reviewed. The main outcome measures were intraocular pressure (IOP), best-corrected visual acuity (BCVA), number of antiglaucoma medications, and postoperative complications. Surgical success was defined as last IOP ≤21 mmHg or ≥6 mmHg and without loss of light perception. Results. The mean follow-up duration was 11.7 ± 5.5 (range, 6–23) months. The mean IOP before the AGV implantation was 37.9 ± 6.7 mmHg with an average of 3.5 ± 1.2 drugs. At the final visit, the mean IOP was 15.9 ± 4.6 mmHg (p=0.001) and the mean number of glaucoma medications decreased to 2.3 ± 1.3 (p=0.021). At the last visit, 11 eyes (84.4%) had stable or improved VA and one eye (7.7%) had a final VA of no light perception. Surgical success was achieved in 11 of the 13 eyes (84.4%). Postoperative complications were bleb encapsulation (69.2%), early hypotony (38.5%), hyphema (23.1%), decompression retinopathy (23.1%), choroidal detachment (15.4%), intraocular hemorrhage (7.7%), and late endophthalmitis (7.7%). One eye (7.7%) was enucleated because of late endophthalmitis. Conclusions. Despite complications necessitating medical and surgical interventions, vitrectomized eyes were effectively managed with AGV implantation.